Band engineering in Mg3Sb2 by alloying with Mg3Bi2 for enhanced thermoelectric performance. Issue 1 (11th December 2017) - Imasato, Kazuki; Kang, Stephen Dongmin; Ohno, Saneyuki; Snyder, G. Jeffrey
Abstract : The optimum Mg3 Sb2 –Mg3 Bi2 alloy composition for thermoelectrics is modeled by analyzing transport properties and understanding changes in the electronic structure. Abstract : Mg3 Sb2 –Mg3 Bi2 alloys show excellent thermoelectric properties. The benefit of alloying has been attributed to the reduction in lattice thermal conductivity. However, Mg3 Bi2 -alloying may also be expected to significantly change the electronic structure. By comparatively modeling the transport properties of n- and p-type Mg3 Sb2 –Mg3 Bi2 and also Mg3 Bi2 -alloyed and non-alloyed samples, we elucidate the origin of the highest zT composition where electronic properties account for about 50% of the improvement. We find that Mg3 Bi2 alloying increases the weighted mobility while reducing the band gap. The reduced band gap is found not to compromise the thermoelectric performance for a small amount of Mg3 Bi2 because the peak zT in unalloyed Mg3 Sb2 is at a temperature higher than the stable range for the material. By quantifying the electronic influence of Mg3 Bi2 alloying, we model the optimum Mg3 Bi2 content for thermoelectrics to be in the range of 20–30%, consistent with the most commonly reported composition Mg3 Sb1.5 Bi0.5 .